Bandgap engineering in Mn3TeO6: giant irreversible bandgap reduction triggered by pressure. Issue 80 (16th September 2019) - Liu, Lei; Skogby, Henrik; Ivanov, Sergey; Weil, Matthias; Mathieu, Roland; Lazor, Peter
Abstract : The quenchable phase of multiferroic oxide Mn3 TeO6 with narrowing bandgap of 1.86 eV was synthesized by high-pressure treatment. Abstract : In this study, the bandgap energy of the multiferroic oxide Mn3 TeO6 is successfully reduced by ∼39% from 3.15 eV to 1.86 eV, accompanied by a phase transition at high pressures. The high-pressure phase with smaller bandgap energy is quenchable to ambient conditions and represents a promising light-harvesting material for photovoltaic applications.